SUPERVISORY BOARD DIVERSITY AND POLITICALLY CONNECTED COMPANIES PERFOMANCE - Desi Ilona; Zaitul Zaitul; Eugene Okyere-Kwakye; Rina Asmeri (Jurnal ASET (Akuntansi Riset), 2022)
Main Purpose - This study examines whether board diversity is lower in politically connected companies than in non-political affiliated companies and determines whether board diversity is less effective in a politically connected company.Method - Using 651 companies-years observation, the univariate analysis using the independent t-test and mean to see any significant difference of board diversity in the politically connected company vs non-connected companies. Besides, multiple regression analysis is employed to determine the effectiveness of board diversity in two types of companies. Main Findings – This study found that board diversity (national, gender, and experience diversity) is lower in politically connected companies, and there is a significant difference between these types of companies. Besides, board diversity is less effective in political companies than in non-political affiliated companies.Theory and Practical Implications - This study implies that politically connected companies should increase board diversity and its effectiveness to boost their performance. Theoretically, this study found that the resources dependent and agency theories are not sound in politically connected companies. Novelty – This study provides insightful discussion about whether board diversity is worthwhile in politically connected companies in the unique continental European corporate governance system, Indonesia, where there was little discussion from previous studies.